Can teaching be taught? Improving teachers' pedagogical skills at scale in rural Peru - Juan Francisco Castro; Paul Glewwe; Alexandra Heredia-Mayo; Stephanie Majerowicz; Ricardo Montero (Quantitative Economics, 2025)
We evaluate the impact of a large-scale teacher coaching program in Peru, a context with high teacher turnover, on teachers' pedagogical skills and student learning. Previous studies find that small-scale coaching programs can improve teaching of reading and science in developing countries. However, scaling up can reduce programs' effectiveness, and teacher turnover can erode compliance and cause spillovers onto non-program schools. We develop a framework that defines different treatment effects when teacher turnover is present, and explains which effects can be estimated. We evaluate this teacher coaching program, exploiting random assignment of that program's expansion to 3797 rural schools in 2016. After two years, teachers assigned to the program increased their aggregate pedagogical skills by 0.20 standard deviations. The program also increased student learning; after 1 year, Grade 2 students' mathematics and reading scores increased by 0.106 and 0.075 standard deviations (of the distributions of those test scores), respectively. After three years, the cumulative effect increases slightly, to 0.114 and 0.100, respectively. One reason why these impacts are low is that some uncoached teachers moved into treated schools in years 2 and 3. Following our framework, we estimate that the impacts on students of having a "fully" coached teacher for all three years are 0.18 and 0.16 standard deviations for mathematics and reading comprehension, respectively.
https://doi.org/10.5281/zenodo.13738582
Keywords: I21; O15; 330; Education; teacher coaching; pedagogical skill; student learning; teacher turnover